2018
DOI: 10.1002/ijc.31283
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of antibody response to Streptococcus gallolyticus and risk of colorectal cancer

Abstract: The gut microbiome is increasingly implicated in colorectal cancer (CRC) development. A subgroup of patients diagnosed with CRC show high antibody responses to Streptococcus gallolyticus subspecies gallolyticus (SGG). However, it is unclear whether the association is also present pre-diagnostically. We assessed the association of antibody responses to SGG proteins in pre-diagnostic serum samples with CRC risk in a case-control study nested within a prospective cohort. Pre-diagnostic serum samples from 485 firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…Additionally, 7% of non-advanced adenomas were double-positive to Pil1A-Pil1B, compared to 0% of controls ( p -value < 0.0001) (Butt et al, 2017 ). Data from a recent nested case-control study confirm previous observations that single marker panels are not sufficient to identify CRC patients and adenomas (Butt et al, 2017 , 2018 ). This is potentially due to significant heterogeneity in IgG response between patients and depends on the antigenicity of the strain triggering the immune response.…”
Section: Clinical Infections and Host-immune Response Due To Sbsec Insupporting
confidence: 69%
“…Additionally, 7% of non-advanced adenomas were double-positive to Pil1A-Pil1B, compared to 0% of controls ( p -value < 0.0001) (Butt et al, 2017 ). Data from a recent nested case-control study confirm previous observations that single marker panels are not sufficient to identify CRC patients and adenomas (Butt et al, 2017 , 2018 ). This is potentially due to significant heterogeneity in IgG response between patients and depends on the antigenicity of the strain triggering the immune response.…”
Section: Clinical Infections and Host-immune Response Due To Sbsec Insupporting
confidence: 69%
“…Follow-up of a colon cancer patient in Spain revealed that antibody response to pilus protein Gallo 2039, Gallo2178, and Gallo 2179 has been associated with an increased risk of colon cancer [13]. Antibody response to S. gallolyticus is mounted prior to emergence of malignancy in the colonic tissue [14].…”
Section: Discussionmentioning
confidence: 99%
“…[88][89][90] A prospective study recently associated a commensal candidate, Streptococcus gallolyticus subspecies gallolyticus (SGG) with the risk to develop CRC, since anti-SGG IgG were more frequently present in individuals who developed cancer later in life (Table 2). 91 Although a causative link between the presence of such species and CRC has not been demonstrated, certain anti-commensal IgA 92 or IgG 91 reactivities might constitute potential diagnostic biomarkers for CRC. The detection of anti-commensal IgG might also offer novel opportunities for predicting immunotherapy efficacy in the treatment of cancers.…”
Section: Anti-commensal Igg and Cancermentioning
confidence: 99%